(untitled) (Samarra Journal of Pure and Applied Science, 2026)
Higher education institutions in developing countries continue to struggle with certificate authenticity due to the limitations of centralized verification systems. Although blockchain-based certificate verification offers a secure and transparent alternative, adoption intention remains low because behavioral determinants are insufficiently understood. This study develops and tests an integrated model combining Technology Readiness Index dimensions, diffusion of innovation factors, perceived complexity, compatibility, and resistance to change to explain intention to adopt blockchain-based certificate verification. Results indicate that innovativeness, optimism, discomfort, insecurity, and perceived compatibility significantly influence adoption intention, while perceived complexity is not significant. Resistance to change selectively moderates the effects of innovativeness and discomfort but no other predictors. The model demonstrates strong explanatory power, emphasizing the dominant role of psychological readiness and behavioral resistance over purely technical concerns. The study extends blockchain adoption literature by integrating multiple theoretical perspectives in an educational context and provides practical guidance for capacity building, training, and change management to support blockchain implementation in developing higher education systems